PERBAIKAN ATURAN KUADRATUR NEWTON-COTES TERTUTUP - Dina Oktavieny; Bustami '; Imran M. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses the improvement of closed Newton-Cotes quadrature rules. The idea is based on deriving weights of closed Newton-Cotes quadrature rules having the same length of intervals using degree of accuracy. By including the lower limit of the integral and the width of the interval as the two new additional variables,we obtain weights, the lower limit and the width of the interval used to form the improvement of closed Newton-Cotes quadrature rules. Computational tests using examples show that the accuracy of improvement formula is better than closed Newton-Cotes quadrature rules.